ANALISIS FAKTOR YANG MEMPENGARUHI KINERJA POSYANDU DI KABUPATEN PASER TAHUN 2021 - Rusmalayana; Muhlis Hafel; Muh. Jamal (Journal Publicuho, 2023)
To analyze the factors that affect the performance of posyandu in Pasar District. Analytical survey research with a cross sectional study design. The sample is 76 cadre coordinators using Cluster Proportional Random Sampling. The research instrument used a questionnaire. Descriptive and statistical data analysis, namely chi square and multiple logistic regression. posyandu whose cadres receive training will perform well (p=0.000). Posyandu whose cadres are rewarded according to their performance standards will comply (p=0.011). Posyandu with complete or supportive infrastructure will have good performance (p=0.000), Posyandu with combined financing sources will have good performance (p=0.001). The analysis using multiple logistic regression showed the variables of infrastructure (p=0.003; Exp.B=13,935), training (p=0.004; Exp.B=9.980), rewards (p=0.009; Exp.B=11,685) and sources of financing ( p=0.028; Exp.B=7.168) with 95% confidence level. There is an effect of training, rewards, infrastructure and sources of financing with posyandu performance. Suggestion: The health office includes cadres in training, increases cadre rewards, completes facilities and infrastructure and increases community participation to support posyandu financing.